This preview shows page 1. Sign up to view the full content.
Unformatted text preview: = dgh + gdh dx dx dx f(x)=x2(x 1) df = 2(-129 +2 dx Iff(x)=g(x),then df = 1 - h(x) dx h2 dx dx f(x)= x2 df = 1 2(7 +29 -2 (7 +29 dx (7 +292 Example: 6. Logs and Exponentials Example: 7. The Chain Rule Example: If f(x) = ln(x), then df = 1x dx Iff(x)=ex,then df = dx If f(x) = eg(x), then df = dgeg(x) dx dx f(x) = ex2 df = 2xex2 dx Ifz=f(y)and y=g(x),then dz = dfdy dx dy dx z=y2,y=(x2+3x) dz = 2 2 + 3 ( 2 +329 dx...
View Full Document
This note was uploaded on 04/05/2012 for the course ECN 437 taught by Professor Peterwilcoxen during the Spring '12 term at Syracuse.
- Spring '12